TINJAUAN YURIDIS TERHADAP SURAT DAKWAAN DENGAN ASAS CONCURSUS REALIS DALAM PERKARA LAKALANTAS DI PENGADILAN NEGERI TANAH GROGOT - Ratih Febriyanti (Journal of Law ( Jurnal Ilmu Hukum ), 2021)
ABSTRACTThe Indictment is a limitation of prosecution. A defendant cannot be charged or found guilty and punished for an act that is not listed in the Indictment. Criminal acts regulated in Article 65 to Article 70 of the Criminal Code concerning the accumulation or combination of criminal acts known as Concursus Realist, such as an example of a traffic accident in the jurisdiction of Paser City which resulted in a motorized vehicle user being seriously injured and lightly injured. The problems raised in this paper are how the provisions of the indictment for the cumulation in the discourse and what are the legal provisions of the indictment with the principle of realist discourse in the accident case at the Tanah Grogot District Court. This type of research is a normative juridical research with a problem approach that is used in the writing of this thesis is by means of a statutory approach.The results of the study show that the legal provisions of the indictment with the principle of realist discourse in the crime case at the Tanah Grogot District Court that in criminal events containing realist discourses in the compilation of the cumulation indictment, are adjusted to the type of realist concurus as regulated in Articles 65-71 of the Criminal Code. According to these provisions, an event is deemed to contain a realist discourse where the threat of basic punishment is the same if in the case concerned there are characteristics, namely the co-existence of a criminal act in which each criminal act stands on its own. Keywords: Indictment, Concursus Realis, Criminal Investigation Case.